Complex PbTe hopper (skeletal) crystals with high hierarchy - Zhu, Ji-Ping; Yu, Shu-Hong; He, Zhu-Bing; Jiang, Jun; Chen, Ke; Zhou, Xiao-Yuan (Chemical communications (Cambridge, England), 2005)
A facile and mild solution method has been discovered for the synthesis of complex PbTe hopper crystals in large quantities, which are highly similar to the cubic halite skeletal crystals formed from extreme supersaturation in salt lakes existing in nature. This route may provide a new approach to growing other complex semiconductor structures of high hierarchy.